Behavioural drivers of adoption of a refined cropping calendar platform in Northern Ghana - Ofosu-ampong, Kingsley; Masoud, Jalaludeen; Amankwaa-Yeboah, Patricia; Jizorkuwie, Abdul-latif; Abera, Wuletawu (2025)
This report presents a behavioural analysis of farmers and extension agents’ adoption and use of a cropping calendar digital platform following a capacity-building initiative in Tamale and Wa, Northern Ghana in July 2025. The intervention, supported by the CGIAR SFP, aimed to enhance farmers’ access to timely and accurate agro-advisory services through digital platforms, while also assisting extension agents in registering their cluster farmers to facilitate efficient information dissemination. A structured survey involving 68 respondents—comprising 58 males and 10 females, predominantly with tertiary education—was conducted to assess user behaviours across 15 key dimensions, including performance expectancy, trust, accessibility, privacy, and intention to continue use. Findings revealed a high level of engagement and satisfaction with the platform, with over 95% of participants reporting it as effective, easy to use, and trustworthy. Strong continuance intention and self-service capability demonstrated that the tool empowers farmers to make agronomic decisions independently. However, areas such as completeness of information and access to user support showed mixed responses, indicating the need for ongoing content enhancement and user assistance systems. The behavioural insights from this study underscore the transformative potential of digital tools in smallholder agriculture, while highlighting the importance of community-led diffusion, localized content, and inclusive design. The report concludes with actionable recommendations for scaling the platform and strengthening digital agriculture strategies across Ghana